1971
DOI: 10.1113/jphysiol.1971.sp009390
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the liberation of phosphate from the muscles of the human forearm during vigorous exercise and on the action of sodium phosphate on forearm muscle blood vessels

Abstract: 3. Infusions of sodium phosphate into the brachial artery which raised plasma phosphate in the venous effluent from the resting muscles by 400 % had no effect upon the rate of the forearm blood flow. 4. These results do not suggest that the liberation of phosphate plays any significant part in mediating the vasodilatation accompanying vigorous exercise of the muscles in the forearm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Additionally, the range of changes in potassium and osmolarity are probably not great enough to explain the range of blood flow increases seen in contracting muscles during exercise (316,317,431,446). Similar issues apply to other electrolytes (26).…”
Section: Potassium and Osmolaritymentioning
confidence: 99%
“…Additionally, the range of changes in potassium and osmolarity are probably not great enough to explain the range of blood flow increases seen in contracting muscles during exercise (316,317,431,446). Similar issues apply to other electrolytes (26).…”
Section: Potassium and Osmolaritymentioning
confidence: 99%
“…Our hindlimb preparation contained both white-and red-fibered muscle, which may account for the difference between our results and those of Hilton and Chir (3). Barcroft et al (20) reported that phosphate concentrations increased by 20% in blood from contracting human forearm muscle in which blood flow increased tenfold. However, when blood phosphate concentrations were increased as much as fourfold above control by infusion of a mixture of NaH 2 PO 4 and Na 2 HPO 4 , flow did not change.…”
Section: Dog Hindlimb Preparationmentioning
confidence: 99%
“…In this way the roles of oxygen, hydrogen ion, potassium, osmolarity and magnesium have been considered (Haddy & Scott, 1968; Scott, Rudko, Radawski & Haddy, 1970), but none appear to be satisfactory either on the grounds of potency, or ofthe amounts detected in the venous effluent, or both. The role of inorganic phosphate has also been investigated in this manner by Barcroft, Foley & McSwiney (1971). They found that during vigorous exercise of the forearm muscles the phosphate in the venous effluent increased in concentration by 20 %.…”
Section: Introductionmentioning
confidence: 99%